"Don't worry—be happy": The sad state of happiness research in gifted students. (3rd July 2021) - Zeidner, Moshe
ABSTRACT: Achieving happiness is considered to be a high value goal in modern society, associated with manifold positive outcomes. Much of the literature on gifted students focuses on cognitive outcomes, with a paucity of research on positive psychological constructs. The major goal of this paper is to examine the empirical evidence bearing on the happiness of gifted students when compared to their nonidentified students from a positive psychological perspective. The methodology of this study is based on a small-scale meta-analysis of the six available studies providing empirical data on differences among educational groups in their happiness. These six studies included a total of 1632 participants (mean proportion male = 53%), comprised of 713 gifted (61% boys) and 919 nonidentified students (47% boys). Overall, this study failed to reveal mean reliable differences among educational groups in happiness, supporting the position that giftedness is more of a protective resource than a vulnerability factor. Directions for future research in this relatively neglected, yet important, area of research are presented. This paper concludes by contending that gifted students who are happy and also feel they are contributing to the greater good and improving life, are also more likely to flourish and eventually benefit both themselves and society as a whole.